Systemic Regulation of Cancer Development by Neuro-Endocrine-Immune Signaling Network at Multiple Levels - Jiang, Shu-Heng; Zhang, Xiao-Xin; Hu, Li-Peng; Wang, Xu; Li, Qing; Zhang, Xue-Li; Li, Jun; Gu, Jian-Ren; Zhang, Zhi-Gang (Frontiers in Cell and Developmental Biology, 2020)
The overarching view of current tumor therapies simplifies cancer to a cell-biology problem in which neoplasms are caused solely by malignant cells and the exploration of carcinogenesis and tumor progression largely focuses on somatic mutations and other genetic abnormalities of cancer cells. The limited therapeutic response indicates that cancer is driven not only by endogenous oncogenic factors and reciprocal interactions within the tumor microenvironment, but also by complex systemic processes. Homeostasis is the fundamental premise of health, and is maintained by systemic regulation of neuro-endocrine-immune axis. Cancer is also a systemic disease that manifested by dysfunction of the nervous, endocrine, and immune systems. Multiple axes of regulation exist in cancer, including central-, organ-, and microenvironment-level manipulation. At each specific regulatory level, the tridirectional communication among the nervous, endocrine, and immune factors transmit flexible signaling to induce proliferation, invasion, reprogrammed metabolism, therapeutic resistance, and other malignant phenotypes of cancer cells, resulting in the extremely poor prognosis of this lethal disease. Understanding this coordinated signaling network will enable the development of new approaches for cancer treatment via behavioral and pharmacological interventions.